Characteristics of Morphology, Reproductive and Physiological Response of Swamp Buffalo on Different Lands in West Aceh Regency - Riki Rahmatullah; Sayed Umar; Ristika Handarini (Randwick International of Social Science Journal, 2024)
Swamp buffaloes are among the most sought-after livestock for meat production in West Aceh Regency. Therefore, an analysis of their production and reproduction is necessary to determine the direction for potential development. The objective of this research is to analyze the characteristics of morphology, reproductive efficiency, and physiological response of swamp buffaloes in different plains in West Aceh Regency. The study was conducted in West Aceh Regency on different plains, including coastal plains and undulating plains, from May to September 2023. The variables measured include quantitative traits, reproductive efficiency, and physiological response, evaluated based on rectal temperature, with a total of 200 animal samples and 100 respondents. The analysis used multiple linear regression and t-test. The research results indicate that the most common quantitative traits such as body length, chest width, chest circumference, hip width, and body weight are influenced (P<0.05) by different plain conditions. Productive performance in terms of age at first marriage variable and reproductive efficiency is influenced (P<0.05) by different plain condition. The physiological response of buffaloes shows that rectal temperature is influenced (P<0.05) by different plain conditions. These both conditions also impacted the quality of swamp buffaloes’ meats that could impact the income of breeders.